Overcurrent relay coordination tool for radial distribution systems with distributed generation - Poonyapa Sookrod (2018)
© 2018 IEEE. The conventional structure of distribution systems is evolving rapidly due to the high penetration of distributed generation (DG). DG may have a detrimental effect on protection coordination of overcurrent relays regarding varying short circuit levels. Overcurrent relays are necessary to ensure the reliability of power system by avoiding malfunction and the unnecessary outage of the healthy part of the system. The relay settings have to be changed depending on capacity and location of installed DG. It is complexity to analyze all operating conditions. Therefore, the effects of DG presence on the existent relays must be investigated in order to maintain protection coordination. To overcome relay coordination problem, overcurrent relay coordination tool is proposed in this paper. This tool is developed using concept of adaptive protection scheme. Relay setting parameters are set automatically in response to changing systems. Furthermore, this proposed tool is suitable for the complex future radial distribution systems.